The Impact of Global Value Chain (GVC) Participation on the Productivity of Manufacturing Firms in Indonesia - Ariiq Arrahman Endito; Mohamad Dian Revindo; Indri Br Situmorang (Universitas Mercu Buana, 2026)
Participation in Global Value Chains (GVCs) has the potential to enhance firm productivity, a critical issue given that Indonesia’s manufacturing productivity still lags behind several Asian economies. However, the level of participation of Indonesian firms in global production networks remains relatively limited, and empirical studies that specifically examine the relationship between international trade participation and manufacturing firm productivity in Indonesia are still scarce. This study aims to analyze the impact of firm participation in GVCs, proxied by international trade activities, including exporting, importing, and simultaneous exporting and importing, on the productivity of manufacturing firms in Indonesia. The analysis employs cross-sectional data from the 2017 Industrial Survey (SI/IBS) conducted by BPS-Statistics Indonesia. The Ordinary Least Squares (OLS) method is used to estimate firms’ Total Factor Productivity (TFP). The estimation results indicate that all forms of international trade participation are positively and significantly associated with firm productivity. The largest effect is observed among import-only firms. These findings suggest that firm engagement in international trade, particularly through the use of imported inputs, is linked to higher productivity in Indonesia’s manufacturing sector. Therefore, policies aimed at enhancing trade integration and improving access to imported inputs may serve as important channels for boosting manufacturing productivity.